A Swift Algorithm and Hue-Preserving Based Mechanism for Underwater Image Colour Enhancement - Soni, Vishnu; Sharma , Abhay; Rajpurohit , Jitendra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Underwater images often exhibit colour variations and poor perceptibility due to wavelength dependent light absorption and scattering. In order to address these problems, we introduce a swift algorithm and hue-preserving based mechanism for an effective and reliable underwater image enhancement. In order to reduce the excessive pixel values, we initially used a simple logarithmic function as a preprocessing step. The brightness and contrast are then altered using a novel nonlinear enhancement operation that was developed empirically on the basis of mathematical, statistical and spatial data. Additionally, as a post-processing step, a regularisation function is used to rearrange image pixels in the natural dynamic range. We also used CHS and WDF techniques which perform on HIS and HSV colour models, respectively. Prior to applying a WDF method to the S and I components, the degraded images are initially transformed from RGB color model to HIS colour model. This model preserves hue component H. The image is then changed in the HSV color model in a similar way, with the H component being kept invariant and the S and V components being process using CHS method. Experimental findings shows that the enhancement of image quality in terms of qualitative and quantitative evaluation in the proposed method. Our method has been demonstrated successfully enhancing underwater images having colour distortion, poor contrast and detail loss.